INFLUENCES OF RESISTANT POWER EXERCISE WITH INTAKE KARNITIN SUPPLEMENT TO IMPROVEMENT FREE FAT ACID AND VO2 MAX - Soesanto, Wibisono (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2012)
Sport achievement basically depends on four main factor readiness, that are physical, technical, tactical and mental readiness (Bompa, 1990). Physical readiness is a base or foundation for sport achievement, because superfine physical ability will also provide fine technical, tactical and mental ability. Athletes physical ability determined by one of the main body fit parameters, that is VO2 max. This study wants to measure the difference between influences of endurance exercise with carnitine supplement administration and endurance exercise without carnitine supplement administration toward the increased free fatty acid and VO2 max.This is a kind of experimental study and, according to the place, is a field experiment with Randomized Pretest â Posttest Control Group Design. Treatment at group 1 was provided continual endurance exercise with low intensity three times a week for two months supplemented with carnitine administration of 1.6 g carnitine/exercise. Group 2 was provide endurance exercise treatment continually with low intensity 3 times a week for two months supplemented with carnitine administration of 0.8 g carnitine/exercise and group 3 was provided with continual endurance exercise with low intensity 3 times a week for two months. After the treatment completed for two months, each tested person from group 1 through group 3 was given a posttest by their blood sample withdrawal to measure Free Fatty Acid using Calorimetric method and VO2 max measurement using Treatmill.With anova statistic it was obtained F = 11.924 and p = 0.000. Because p < 0.05, then, there was a significant difference of Free Fatty Acid for the three study groups. Group 1 increment (1.6 g of carnitine supplement each continual endurance exercise with low intensity) was higher than group 2 (0.8 g of carnitine supplement for each continual endurance exercise with low intensity) and group 2 increment (administration of 0.8 g carnitine supplement each continual endurance exercise with low intensity) was higher than group 3 (continual endurance exercise with low intensity without carnitine supplement administration). With anova statistic test it was obtained F = 23.756 and p = 0.000. Because p < 0.05, then, there was difference meaning of VO2 max for the three study groups. Group 1 increment (1.6 g carnitine supplement administration each continual endurance exercise with low intensity) was higher than group 2 (0.8 g carnitine supplement administration for each continual endurance exercise with low intensity) and group 2 (0.8 carnitine supplement administration for each continual endurance exercise with low intensity) was higher than group 3 (continual endurance exercise with low intensity without carnitine supplement)